(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
The Bonarelli Level (BL) is a radiolarian-ichthyolithic, organic-rich marker bed that was deposited close to the Cenomanian/Turonian boundary (CTB) representing the sedimentary expression of the global Oceanic Anoxic Event 2 (OAE2). In northeastern Italy this horizon yielded fossil remains documenting a rather diverse ichthyofauna. The assemblage was studied by Sorbini in 1976 based on material from a single locality, Cinto Euganeo. Subsequently, other localities yielding fish remains have been discovered. Our revision also includes fish remains from three new fish-bearing localities, the Carcoselle Quarry, the Valdagno-Schio tunnel and Quero other than those from Bomba Quarry near Cinto Eugeneo. At least 28 taxa were identified, including nine previously not reported from the Bonarelli Level, namely: Scapanorhynchus raphiodon, Cretalamna appendiculata, Archaeolamna kopingensis, ‘Nursallia’ tethysensis, Belonostomus sp., Dixonanogmius dalmatius, ‘Protosphyraena’ stebbingi and the beryciform Hoplopteryx sp. The overall assemblage mostly consists of crossognathiforms, tselfatiiforms and aulopiforms. A comparison of the taxonomic diversity with coeval assemblages evidences a general similarity with nearby western Tethyan fish assemblages and especially with the Jebel Tselfat ichthyofauna, although some of the taxa are exclusively shared with the assemblages of the boreal realm (English Chalk, Westphalia and Saxony). However, additional information would be necessary to more properly define the main global ichthyogeographic patterns during the Cenomanian.